PENERAPAN MODEL PEMBELAJARAN THINKING ALOUD PAIR PROBLEM SOLVING DAN PROBLEM BASED LEARNING PADA MATERI TRANSFORMASI - Sengkey, Dwi Jeanita; Sulangi, Victor; Mangobi, James (Universitas Negeri Manado, 2020)
ABSTRACT. The aim of this research is to know the differences in student learning outcomes on transformation lesson between group of students who used the thinking aloud pair problem solving (TAPPS), problem based learning (PBL) model and direct instruction model. This research was conducted at SMPN 1 Kawangkoan during the odd semester of the 2019/2020 academic year. The subjects of this research were students of class IX-A as the 1st experimental class, class IX-B as the 2nd experimental class and class IX-C as the control class. The results of hypothesis test Shown that there were significant differences in the average learning outcomes between students who use the TAPPS, PBL, and direct instruction model on transformation lessons.Keywords: TAPPS, PBL, Direct Instruction